Damage Control and the Open Abdomen: Challenges for the Nonsurgical Intensivist. (October 2016) - Griggs, Cornelia; Butler, Kathryn
Background: As strategies in acute care surgery focus on damage control to restore physiology, intensivists spanning all disciplines care for an increasing number of patients requiring massive transfusion, temporary abdominal closures, and their sequelae. Objective: To equip the nonsurgical intensivist with evidence-based management principles for patients with an open abdomen after damage control surgery. Data Source: Search of PubMed database and manual review of bibliographies from selected articles. Data Synthesis and Conclusions: Temporary abdominal closure improves outcomes in patients with abdominal compartment syndrome, hemorrhagic shock, and intra-abdominal sepsis but creates new challenges with electrolyte derangement, hypovolemia, malnutrition, enteric fistulas, and loss of abdominal wall domain. Intensive care of such patients mandates attention to resuscitation, sepsis control, and expedient abdominal closure.